2023
DOI: 10.1177/23779608221150725
|View full text |Cite
|
Sign up to set email alerts
|

Developing and Testing Digital Ethical Reflection in Long-Term Care: Nurses’ Experiences

Abstract: Introduction Nurses working in municipal long-term care face ethical challenges that can lead to moral distress and discomfort for the nurse and affect the quality of patient care. Tools and methods that contribute to increased ethical awareness and support for nurses dealing with moral issues are lacking. Technological innovations may be suitable for ethics work, but little research has been conducted on how such solutions could be designed or their potential benefit. Therefore, this study contributes knowled… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 73 publications
0
1
0
Order By: Relevance
“…The present study underscores the importance of co-worker support in RNs’ work satisfaction, agreeing with a previous finding on co-worker support being crucial for retention [ 15 ]. However, RNs are missing opportunities to reflect upon ethical dilemmas and experience a lack of support from their managers [ 31 ]. Furthermore, RNs’ personal contacts may not be able to provide them with the needed support due to patient confidentiality limitations in HHC [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…The present study underscores the importance of co-worker support in RNs’ work satisfaction, agreeing with a previous finding on co-worker support being crucial for retention [ 15 ]. However, RNs are missing opportunities to reflect upon ethical dilemmas and experience a lack of support from their managers [ 31 ]. Furthermore, RNs’ personal contacts may not be able to provide them with the needed support due to patient confidentiality limitations in HHC [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Organizations should also support informal learning processes to enhance the process of learning from everyday work (Sujan, 2015; Sujan et al, 2017). New tools and methods, such as digital ethical reflection tools, could become a tool for managers in their support for employees who face ethical challenges when providing long‐term care (Jakobsen et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…Evidence from the literature describes initiatives emphasising the value of reflection, for example, by forming ethics reflection groups and the ethics round. Although it is suggested that discussing norms and values with colleagues contributes to a sense of reflective and moral conformity and fosters an ethical climate (6), nurse managers should also be…”
mentioning
confidence: 99%